Offshoring and the new insecurities: towards new types of ''white collar consciousness'' in Germany in globalised working environments. (1st April 2010) - Andreas Boes; Tobias Käämpf
Abstract : This paper looks at the effects of the globalisation and economisation strategies of IT companies on the work experiences, consciousness and ''interest orientations'' of highly-qualified employees in the field of software development and services. Drawing on a range of qualitative research projects, the authors explore the ways in which the interest orientations of white-collar workers in the IT industry have changed. They conclude that a new insecurity is emerging concerning work content and job stability even on the part of these highly-qualified employees. They mostly ascribe this to the pressures of internationalisation and, more specifically, to the offshoring strategies of companies. As a result, the traditional ''focus on contribution'' of highly-quaified workers is being eroded. This change in interest orientation is complex and partially contradictory. Nevertheless, there is a distinct tendency toward a new employee orientation among these white-collar workers. It remains to be seen in what direction this orientation will develop and, more specifically, what forms of action will emerge in pursuit of these perceived interests.